In vitro photodynamic therapy of Candida albicans, the cause of vulvovaginal candidiasis, is enhanced by Bacillus and Enterococcus probiotics - Zeinab Ghanbari; Ali Makhdoumi (Photodiagnosis and Photodynamic Therapy)
Background: Candida albicans is the primary cause of vulvovaginal candidiasis, a worldwide health concern for women. The use of supplemental methods, such as antimicrobial photodynamic therapy (aPDT) and probiotics, was promoted by the ineffectiveness of the existing antifungal drugs. Methods: This study examines the combined effects of probiotics (Bacillus and Enterococcus isolated from the fermented pickles) and PDT (using red laser (655 nm, 18 J/cm2) as a light source and methylene blue dye (30 mg/mL) as a photosensitizer) on the in vitro virulence activity of C. albicans including growth, biofilm formation, antifungal resistance, biofilm elimination, and biofilm dispersion. Results: The probiotic strains demonstrated a higher resistance to PDT compared to the fungal cell. Bacillus and Enterococcus enhanced the antifungal effects of PDT on planktonic Candida cells in both pre-PDT and post-PDT interactions. The inhibition of biofilm formation by PDT was improved upon interaction with Bacillus (70 %) and Enterococcus (58 %). The eradication of Candida biofilm using PDT was increased after a combination with Bacillus (67 %) and Enterococcus (46 %). The nystatin resistance of the fungal biofilm following PDT treatment was decreased from (µg/ml) 25 to 6.25 due to the interaction with both probiotic strains. Fungal cell dispersion from the biofilm after PDT treatment diminished by 18 % and 25 % in the presence of Bacillus and Enterococcus strains. Galleria mellonella mortality was significantly changed following the PDT of the fungi/probiotic-injected larvae. Conclusions: This synergistic activity suggests the use of probiotics/PDT as a supplemental treatment for vulvovaginal candidiasis.